"Solo és mãe gentil": a questão de pintura de paisagem : caráter e natureza do Brasil - Santos, Amandio Miguel dos (1993)
Man sees and adapts nature to his own interests. He humanizes or destroys it turning it into something for himself or under his control, or desires to draw a pleasant or picturesque interpretation from it. The notion of nature, or that which we from of it is a cultural idea. Depending on the period in time and on the medium by whose means it is expressed, the idea of nature or any other sense attributed to it has, in the art/nature context, a set of multiple mirrors with questions such as whether art reflects nature, or nature is the mirror of art. Art in Brazil witnesses the emergence of landscape painting in the production of images by traveler painters who came here searching either for the exotic in such landscapes, or moved by the desire to document what they saw, thus gradually providing vast material for the production of iconography albums that were published both in European and Brazilian cultural centers. In Brazilian culture, the art/nature context takes on a fleeting and mysterious profile. The interpretation of paintings depicting nature has never represented an abstract idea in Brazil. On the contrary, it has always been evoked either as the domain of order, or as the rehabilitation of chaos. The first pictorial representations of Brazilian landscapes were those of the 17th century painter, Frans Post. In them, Post reveals a fascination for the landscapes of the unknown. The lands of the New World exercised on him an enigmatic revelation of man faced with the natural world. In the 18th century, it was Leandro Joaquim who first had the objective of narrating the history of his own home town scenographically. His aim was to document the various localities as they would appear to the eyes of a vision. He materialized the discovery of nature as an esthetic phenomenon in his pictures. However, in the 19th century, with the implementation of the official teaching by the Imperial Academy of Fine Arts, landscape painting was required to be subordinated to the principal themes of paintings and become a mere complement to them. Nevertheless, it was through the traveler painters that the observations of nature became the center of interest for the appreciation of the natural world, whose whole esthetic potential had not been explored and discovered in the previous centuries of Art in Brazil. Thus, this dissertation aims to interpret/analyse the visual production of the artists who, faced with the esthetic discovery of the landscapes of the “New World”, postulated a new set of image-based concepts.